2021
DOI: 10.1109/tnsre.2021.3105644
|View full text |Cite
|
Sign up to set email alerts
|

Efficient TMS-Based Motor Cortex Mapping Using Gaussian Process Active Learning

Abstract: Transcranial Magnetic Stimulation (TMS) can be used to map cortical motor topography by spatially sampling the sensorimotor cortex while recording Motor Evoked Potentials (MEP) with surface electromyography (EMG). Traditional sampling strategies are time-consuming and inefficient, as they ignore the fact that responsive sites are typically sparse and highly spatially correlated. An alternative approach, commonly employed when TMS mapping is used for presurgical planning, is to leverage the expertise of the coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In future work, we plan to include cortical motor topography mapping using active learning [23] and to study the generation of the volume conductor model by deep learning, to determine if we can combine these with the current expert user-guided mapping and the segmentation-finite element simulation pipeline, respectively, or perhaps even replace either or both entirely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In future work, we plan to include cortical motor topography mapping using active learning [23] and to study the generation of the volume conductor model by deep learning, to determine if we can combine these with the current expert user-guided mapping and the segmentation-finite element simulation pipeline, respectively, or perhaps even replace either or both entirely.…”
Section: Discussionmentioning
confidence: 99%
“…The details of these preprocessing techniques are outlined in Section II-C. For each map, TMS (100-300 stimulations, 4 s ISI) was delivered over a 6×6 cm regular grid (1 cm spacing, 36 cm 2 area) centered on the hotspot. For each intensity, one stimulus was delivered to each of the 49 equidistant points on the grid, and the remaining stimulations were delivered using real-time feedback from the MEPs to maximize information about the responsive areas [5], [22], [23]. Care was taken to ensure that the mapping included the full extent of the excitable area for all recorded muscles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in the primary publication 1 and elsewhere, 2 , 3 , 4 , 5 , 6 Gaussian-process (GP)-based Bayesian optimization (BO) algorithms are a powerful framework to automatically optimize the efficacy of neurostimulation. It has been shown to outperform other strategies to simultaneously find the optimal values of multiple stimulation parameters (i.e., the optimal combination of parameter values) to maximize a chosen feature of the evoked response (e.g., the movement amplitude or the electromyographic [EMG] burst amplitude).…”
Section: Before You Beginmentioning
confidence: 99%
“…The remaining stimuli (51-251 per intensity for subject 1 and 250-251 per intensity for subjects 2 and 3) were delivered within the 6x6 cm area defined by the grid at loci selected by the expert TMS operator using real-time feedback from the MEPs to maximize information about the responsive areas. We have previously shown that this technique produces similar information to traditional gridded mapping approaches [24]. Care was taken to ensure that the mapping included the full extent of the excitable area at the given stimulation intensities for all recorded muscles.…”
Section: A Data Acquisitionmentioning
confidence: 99%